Chaetothyrina mangiferae sp. nov., a new species of Chaetothyrina - Singtripop, Chonticha; Hongsanun, Sinang; Li, Junfu; de Silva, Nimali Indeewari; Phillips, Alan J.l.; Jones, Gareth E.b.; Bahkali, Ali H.; Hyde, Kevin D. (Phytotaxa, 2016)
Chaetothyrina musarum and C. mangiferae sp. nov. (Micropeltidaceae, Dothideomycetes) are reported from fruits of Musa sp. (Musa acuminata × Musa balbisiana) and Mangifera indica, respectively. Introduction of a new species, Chaetothyrina mangiferae, and provision of a reference specimen for C. musarum with sequence data, supported by morphology will help to stabilize the taxonomy of the genus and family. Maximum likelihood and Bayesian analyses of LSU and SSU sequence data show that C. musarum forms a distinct clade with other genera in Micropeltidaceae within Capnodiales and C. mangiferae clusters in a poorly supported clade in Dothideomycetes, Illustrated accounts of Chaetothyrina musarum (reference specimen) and C. mangiferae are provided and compared with similar taxa. This is the first report of C. musarum causing sooty blotch and flyspeck disease on Musa sp. (Musaceae) in Thailand and C. mangiferae causing sooty blotch and flyspeck disease of Mangifera indica (Anacardiaceae) worldwide.